Effect of post AI immunotherapy on dynamics of uterine micro flora and conception in subclinical endometritis cows - SINGLA, P; SINGH, JAGIR; SHARMA, N S; DHALIWAL, G S; KUMAR, AJEET (The Indian Journal of Animal Sciences, 2014)
Sub-clinical bacterial endometritis is one of the major causes of conception failure in cows. Treatment with intrauterine administration of antibiotics or antiseptics causes elapse of one estrous cycle and prolongs inter-calving period Immunomodulator (E. coli lipopolysaccharide or lipopolysaccharide + autologous serum) was used as post AI therapy to treat sub-clinical bacterial endometritis. Most common bacteria isolated from uterine swabs were E. coli (31.11 %) followed by Staph. aureus(26.67%), Proteus spp. (6.67%), Pseudomonas spp. (4.44%), Corynebacterium spp. (2.22%) and Bacillus spp. (2.22%). Treatment with lipopolysaccharides (TL) or lipopolysaccharide + autologous serum (T LAs)’ yielded bacteriologically sterile uterine swabs. Bacterial load in uterine washings was around 50 x 103/ml before treatment which decreased significantly (P<0.01) to 9.67 +- 0.73 x 103/ml and 2.86 +- 0.09 x 103/ml 12 hr after treatment in group TL and TLAS respectively. Conception rate increased significantly up to 75% and 80% in TL and TLAS groups, respectively, against only 8.33% in TP (control group).